Physical and Chemical Evaluation of Different Brands of Paracetamol Tablets - Ruwida Kamour; Entesar El-Sharaa; Asma Eswayah (AlQalam Journal of Medical and Applied Sciences, 2024)
Paracetamol is considered as one of the most Over-The-Counter (OTC) analgesic and antipyretic drug used. Therefore, assessment of its chemical content as well as physical tests is important to ensure its therapeutic effectiveness. This work included evaluation of three different brands of paracetamol tablets collected from different community pharmacies in Tripoli-Libya as a part of post-marketing evaluation. The physical tests included weight variation, hardness, disintegration, where chemical test included content uniformity of each brand. Physical tests were varying due to different considerations of manufacturing. Test for content of each product showed that the (A) product was of highest percentage content followed by (B)Panadol with small difference where Panadol from (C) had the lowest value; 92%. The results showed the failure of code (C) drug to comply with pharmacopoeia standards for uniformity of contents.